Synthesis and evaluation of thieno[2,3-d]pyrimidin-4(3H)-ones as potential antitubercular agents - Borate, Hanumant B.; Annadate, Ritesh A.; Vagh, Sandip S.; Pisal, Mahesh M.; Deokate, Sagar B.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Nawale, Laxman U.; Sarkar, Dhiman (MedChemComm, 2015)
A number of thieno[2,3-d]pyrimidin-4(3H)-ones were designed, synthesized and screened against Mycobacteria as a part of our program to develop new antitubercular agents. It was observed that some of the compounds have significant antimycobacterial activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743). The active compounds were studied for cytotoxicity against four cell lines and were found to be non-cytotoxic. The results showed that compounds 13b and 29e were found to exhibit very good antimycobacterial activity (MIC in the range of 6-8 mu M) and the thienopyrimidinones as a class have potential to be developed as antitubercular agents.

Synthesis and evaluation of thieno[2,3-d]pyrimidin-4(3H)-ones as potential antitubercular agents (vol 6, pg 2209, 2015) - Borate, Hanumant B.; Annadate, Ritesh A.; Vagh, Sandip S.; Pisal, Mahesh M.; Deokate, Sagar B.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Nawale, Laxman U.; Sarkar, Dhiman (Medchemcomm, 2016)

Novel synthesis of 3-((benzo[d]thiazol-2-ylamino)(phenyl)methyl)-4-hydroxy-1-methylquinol in-2(1H)-one via consecutive C-C and C-N bond formation in water - Yadav, Maruti B.; Vagh, Sandip S.; Jeong, Yeon Tae (Research on Chemical Intermediates, 2020)
A simple, efficient, and eco-friendly protocol has been developed for the synthesis of novel 3-((benzo[d]thiazol-2-ylamino)(4-methoxyphenyl)methyl)-4-hydroxy-1-met hylquinolin-2(1H)-one derivatives using a one-pot C-C and C-N bond forming strategy from the reaction of 4-hydroxy-1-methylquinolin-2(1H)-one, 2-aminobenzothiazole and aromatic aldehydes in aqueous solvent without using any metal catalyst. Several advantages of this protocol include its operational simplicity, short reaction time, mild reaction condition, efficient utilization of all the reactants, wide functional group tolerance, using water as an environmentally friendly solvent and non-chromatographic purification procedure. [GRAPHICS] .
Keywords: 4-Hydroxy-1-methylquinolin-2(1H)-one; Green solvent; Multicomponent reactions (MCRs); Quinolines; Thiazole

Synthesis of diverse nitrogen fused polycyclic dihydroisoquinoline (DHIQ) derivatives via GBB-based cyclic iminium induced double-annulation cascade - Balwe, Sandip Gangadhar; Vagh, Sandip S.; Jeong, Yeon Tae (Tetrahedron Letters, 2020)
A highly efficient and distinct Bronsted acid-mediated unprecedented cyclic iminium induced double annulation cascade (DAC) protocol for the synthesis of novel dihydroindazolo[30,20:2,3]imidazo[5,1-a]isoquinolinamines has been achieved through the three-component Groebke-Blackburn-Bienayme reaction. The transformation is based on sequential cascade processes involving imine formation followed by an intramolecular nucleophilic substitution to generate a highly reactive cyclic iminium species, which would undergo a rapid [4 + 1] formal cycloaddition steps in one-pot fashion. This strategy provides novel skeletally diverse complex nitrogen fused polycyclic DHIQ derivatives by employing readily available substrates and a simple procedure, which would render this method potentially useful in organic synthesis. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: diversity-oriented synthesis; Excellent yields; GBB-based approach; Novel polycyclic N-fused architecture; Scalable

Divergent annulation of spiro[indoline-pyran] and fused (Epoxyetheno)indeno-furan from 1,2-diketone and 1-cyanoketone - Yadav, Maruti B.; Vagh, Sandip S.; Jeong, Yeon Tae (European Journal of Organic Chemistry, 2022)
A simple and efficient method for the construction of spiro[indoline-pyran] and fused (epoxyetheno)indeno[1,2-b]furan compounds from 1-cyanoketones and 1,2-diketone has been developed. The synthesis proceeded via the Knoevenagel and Michael adduct through intramolecular/Paal-Knorr cyclization under similar reaction condition. The less commonly used 1-cyanoketones and active carbonyl compounds served as the indole containing pyran and bicyclic furan source for the preparation of a new series of heterocyclic compounds. This heterocyclic structure allows one and more than one tetra-substituted carbon center and sequential hexa- and penta-cyclic core under very mild conditions and shows excellent chemo and regioselectivity. In addition, the synthesis of spiro[indoline-pyran] and (epoxyetheno)indeno[1,2-b]furan was demonstrated in a gram scale.
Keywords: Diverse synthesis; Intramolecular; Knoevenagel and Michael adduct; molecular diversity; Oxygen heterocycles; Paal-Knorr cyclization